Influence of aging on opioid dosing for perioperative pain management: a focus on pharmacokinetics - Sebastiano Mercadante (Journal of Anesthesia, Analgesia and Critical Care, 2024)
Abstract The older population continues to grow in all countries, and surgeons are encountering older patients more frequently. The management of postoperative pain in older patients can be a difficult task. Opioids are the mainstay of perioperative pain control. This paper assesses some pharmacokinetic age-related aspects and their relationship with the use of opioids in the perioperative period. Changes in body composition and organ function, and pharmacokinetics in older patients, as well as characteristics of opioids commonly used in the perioperative period are described. Specific problems, dose titration, and patient-controlled analgesia in the elderly are also reviewed. Opioids can be safety used in perioperative period, even in the elderly. The choice of drugs and doses can be individualized according to the surgery, opioid pharmacokinetics, comorbidities, and routes of administration.